Urgent elective pathway service reconfiguration facilitates increased use of surgical adjuncts, improvement in survival trends, and reduced hospital stay for glioblastoma patients. (15th October 2021) - Sun, Rosa; Sharma, Shivam; Petrik, Vladimir; Ughratdar, Ismail; White, Anwen; Zisakis, Athanasios; Watts, Colin; Wykes, Victoria
Abstract: Aims: Glioblastomas (GB) are the most common and aggressive of intrinsic brain tumours. Median survival with maximal therapy is reported to be 14.6 months. Service reconfiguration at the Queen Elizabeth Hospital Birmingham (QEHB) has transformed the service for high grade brain cancer patients, including GB, from a predominantly emergency pathway based system to one of planned urgent-elective admissions consisting of: A. Patient-focused, consultant-led, research orientated "one stop shop" model of integrated outpatient neurosurgical oncology clinic B. Standardisation of urgent elective pathways C. Incorporation of neuro-surgical intra-operative adjuncts (neuro-monitoring, 5-ALA) into routine surgical practice for oncology. Using this model, we have reduced hospital length of stay (with associated financial savings), improved extent of resection and achieved a trend towards increased survival. Method: We retrospectively identified patients with primary histological diagnoses of GB (WHO grade IV), who underwent surgery over a six year period, from 01/01/2014 to 31/12/2019, from the QEHB pathology database. Data was collected for demographics, surgical and oncological therapy, use of intra-operative adjuncts, emergency and elective admission status, year of admission, length of stay (LOS), and extent of resection (EOR) on first post-operative MRI scan from hospital databases. Survival was analysed using the Kaplan-Meier method and independent-samples median testing for survival. Proportion of patients undergoing resective surgery and admission status was calculated by year. Overall median survival was calculated and subgroup comparisons made of patients by: age, admission status, year of admission, biopsy or resection, oncology treatment. Hospital length of stay was calculated for patients by surgical procedure, admission pathways and compared across the year. Financial data taken from averages of inpatient episode costs were used to estimate cost savings. Results: 610 patients underwent primary procedures for GB, of which 64 were still alive at time of analysis (02/02/2021). Median overall survival time was 9.53 months, this was greatest in patients who underwent resection with completion of Stupp protocol: 28.67 months (n=114). From 2014 to 2019, there has been an increase in elective admission rates (28.1% to 90.3%, p<0.001) and increased proportion of resective surgery (68.4% to 81.9%, p<0.001). There is a trend of improved survival from 2014 to 2019 (median 7.95 and 11.08 months, χ2=9.249, p=0.002). Increasing use of intra-operative adjuvants improved EOR (χ2 =31.064, p<0.001). Through improved urgent-elective admission rates, hospital length of stay has decreased by five days for craniotomies and six days for biopsies. Cost analysis of three cases demonstrated that reducing the LOS by one night alone result in an average cost saving of approximately £750 per patient per night. Conclusion: Switching to a system of planned and urgent elective based admission, with standardisation of neuro-oncology patient pathways, increased use of intra-operative adjuncts, earlier oncology multidisciplinary input and outpatient review, has improved the extent of GB resection, led to shorter length of hospital stay associated with significant financial savings and achieved a trend towards increased overall survival.